Examining the Impact of Paternal Control Behavior on Exclusive Breastfeeding: A Cross-Sectional Study in Bogor, Indonesia - Nasution, Ade Saputra; Nuraida, Ida; Putri , Devia Lydia; Raharsari, Rezeki Tri; Waluyo, Darmayanti; Rahim, Eman (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Infants who are not exclusively breastfed often have the potential to experience implications for their future quality of life. Furthermore, the extent of this impact is influenced by the concerted efforts of both the father and mother in promoting and implementing exclusive breastfeeding. Several studies have also shown that father’s proactive support is an essential factor in its successful implementation. Therefore, this study aims to determine the relationship between paternal control behavior and exclusive breastfeeding. A quantitative cross-sectional method was used and the sample population comprised 326 fathers with children aged < 2 years old. The procedures were carried out in the working area of the Situ Udik Health Center in July 2023. The sample size was calculated using the Slovin size formula, followed by the selection of 77 respondents based on the random sampling technique. The data obtained were then analyzed using the chi-square test to assess the association between the variables. The results showed that there was a significant relationship between father's knowledge (p=0.001), attitude (0.006), and trust (p=000.0) with exclusive breastfeeding. Meanwhile, breastfeeding fathers (0.339) and intention (0.341) had no significant influence. Based on these results, father played an essential role in providing support during this practice